Design of the Zeus Forward Tracking Detector - Sherbak, Y. L.; Chernyshov, N. N. (ХНУРЭ, 2010)
The design and construction of the ZEUS forward tracking detector is described. The detector consists of 3 large planar drift chambers mounted in the forward direction with respect to the proton beam and a smaller rear detector of the same type. Test beam measurements performed at DESY show a single wire spatial resolution of 105 μm and a dE/dx resolution of 8.8%. The resolution of the three dimensional track coordinates and slopes provided by one chamber are found to be 90μm and 2.7 mrad, respectively.
Keywords: drift chambers; ZEUS; DESY; test beam measurements